Ultrasound-Assisted Extraction of Total Flavonoids from Corn Silk and Their Antioxidant Activity - Ling-Li Zheng; Guan Wen; Min-Yong Yuan; Feng Gao (Journal of Chemistry)
Object. Ultrasound-assisted extraction of total flavonoids from corn silk and their antioxidant activities were studied. Methods. Response surface methodology was adopted to optimize the extraction conditions and antioxidant activities of the extracted total flavonoids were detected through ferric reducing antioxidant power (FRAP) assay. Results. Through a three-level, three-variable Box-Behnken design of response surface methodology (RSM) adopting yield as response, the optimal conditions were determined as follows: ultrasonic power 500 W, extraction time 20 min, material solvent ratio 1 : 20, and ethanol concentration 30%. Under the optimum conditions, the extraction yield of total flavonoids was 1.13%. FRAP value of total flavonoids extracted from corn silk was 467.59 μmol/L. Conclusion. The total flavonoids of corn silk could be developed as food natural antioxidant reagents.